Macroeconomics : theory and policy - Edgmand, Michael R. (Englewood Cliffs, N.J. : Prentice-Hall, 1979)
This book covers the main elements of macroeconomic theory and policy. It includes extended discussions of inflation, unemployment, and their relationship. As a result, students should gain a better understanding of current policy issues. An attempt has also been made to provide flexibility for instructors who use this book. The material is so organized that students can work through it on their own.
Includes bibliographical references and index.
rpm 04/07/2017
Loans
Keywords: Macroeconomics